Pengaruh Persepsi Wajib Pajak atas Penerapan E-Filing dan Persepsi Wajib Pajak atas Kualitas Sistem E-Filing Terhadap Kepatuhan Pajak - Anisa Widya Larasati; Dyah Probowulan; Achmad Syahfrudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
E-Filing is a system for the achievement of annual report letters (SPT) which is done online and in real time to the Directorate General of Taxes through the official website of the Directorate General of Taxes. This study aims to examine the effect of perceptions of taxpayers on the application of E-filing and perceptions of taxpayers on the quality of e-filing systems for tax compliance in the Jember Pratama KPP case study. This research uses quantitative methods. The number of samples used is 100 taxpayers who use the e-Filing system. The data used in this study are primary data in the form of questionnaires distributed to taxpayer respondents. The results in this study indicate that taxpayer perceptions affect tax compliance and the quality of the e-Filing system has no effect on tax compliance. Keywords: E-Filling, Perception, E-Filing System Quality, Complaints